The Perception of Anthropogenic Global Warming Modeled by Game Theory Decision Tables - Stallinga, Peter; Khmelinskii, Igor (European Scientific Journal, ESJ, 2016)
Society is living in fear of catastrophic climate scenarios, the so called Anthropogenic Global Warming (AGW) theory. It is a multidisciplinary subject; this paper analyzes the psychology behind such thinking which is governing the perception and politics of the subject. It does this in so-called Game Theory decision tables for people’s thinking. We come to the conclusion that current opinion in society will shift from ’active believer’ to ’passive believer’ to ’active non-believer’ if evidence against AGW will continue to accumulate.